The path to a larger life : creating Kentucky's educational future : a report of the Prichard Committee for Academic Excellence. (University Press of Kentucky, 1990)
In the spring of 1989, the Kentucky Supreme Court declared the state's entire system of common schools to be unconstitutional-an epochal decision that will have enormous impact on the future of the commonwealth and its citizens. In the wake of that decision, educational leaders, legislators, and concerned citizens struggle to define Kentucky's educational needs and to find the means to achieve them. The Path to a Larger Life, made up of recommendations from a volunteer citizens' organization, offers the most sweeping analysis of Kentucky's educational needs published in this century. Concentra.